Ecoacoustics : the ecological role of sounds - Farina, Almo; Gage, S. H. (John Wiley & Sons, Inc., 2017)
The sounds produced by geophonic, biophonic and technophonic sources are relevant to the function of natural and human modified ecosystems. Passive recording is one of the most non-invasive technologies as its use avoids human intrusion during acoustic surveys and facilitates the accumulation of huge amounts of acoustical data. For the first time, this book collates and reviews the science behind ecoaucostics; illustrating the principles, methods and applications of this exciting new field. Topics covered in this comprehensive volume include; -the assessment of biodiversity based on sounds emanating from a variety of environments -the best technologies and methods necessary to investigate environmental sounds -implications for climate change and urban systems -the relationship between landscape ecology and ecoacoustics -the conservation of soundscapes and the social value of ecoacoustics -areas of potential future research. An invaluable resource for scholars, researchers and students, Ecoacoustics: The Ecological Role of Sounds provides an unrivalled set of ideas, tools and references based on the current state of the field.